Creep - Tanski, Tomasz; Sroka, Marek; Zielinski, Adam (IntechOpen, 2018)
This book contains 12 chapters with original and innovative research studies in the issues related to the broadly defined creep effect, which concerns not only the area of construction materials but also natural phenomena. The emphasis on the discussion of a new trend of experimental creep testing, which binds the classic creep methods to seek the correlation of parameters obtained in tests, deserves particular attention. This book aims to provide the readers, including, but not limited to, students and doctoral students and also the research personnel and engineers involved in the operation of equipment and structural components as well as specialists in high-temperature creep-resisting materials, with a comprehensive review of new trends in the field of creep-exposed materials and their research methodology. The chapters of this book were developed by respected and well-known researchers from different countries.